Team learning potential in TESOL practice. Issue 3 (9th December 2018) - Stewart, Tim; Dalsky, David; Tajino, Akira
Abstract : The proliferation of "teacher‐proof" scripts for lessons reveals a deep distrust of teachers' intuition and blatant ignorance of the essential humanistic elements underlying education. This model of standardization positions teachers as mere delivery agents of centrally planned curricula based on a hollow promise of effectiveness. We agree that "a good language teacher knows and does but most essentially is " (Arnold & Brown, 1999, p. 4). It follows that a second language teacher who is able to maximize her professional potential in the classroom is, foremost, a learner. This philosophical foundation supports our refinement of the concept of team learning, first proposed by Tajino and Tajino (2000). Our updated model of team learning clarifies the concept by extending discussions of approaches like reflective pedagogy, learner autonomy, and learner‐centered teaching. Team learning opens opportunities for practitioners to expand their role from being exclusively that of a teacher to realizing their learner potential in their own classrooms. The concept of team learning invites teachers to see themselves as team members in learning events. When team learning is achieved, optimal conditions for learning occur that can result in the experience of flow. These conditions, considered as emergent properties, are discussed in this theoretical article.